Iowa Birdline update, November 18, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of Iowa Birdline updates for November 18, 1991. The highlights for the update include sightings of numerous rare birds in Pleasant Creek State Park such as a Pacific Loon, White-winged Scoter and Surf Scoter. Also included are handwritten notes with sightings of several Common Redpolls and an immature White-winged Scoter. Epson - sheet feed/flatbed